Mood and Activity Measured Using Smartphones in Unipolar Depressive Disorder - Tønning, Morten Lindbjerg; Faurholt-Jepsen, Maria; Frost, Mads; Bardram, Jakob Eyvind; Kessing, Lars Vedel (Frontiers in Psychiatry, 2021)
Background: Smartphones comprise a promising tool for symptom monitoring in patients with unipolar depressive disorder (UD) collected as either patient-reportings or possibly as automatically generated smartphone data. However, only limited research has been conducted in clinical populations. We investigated the association between smartphone-collected monitoring data and validated psychiatric ratings and questionnaires in a well-characterized clinical sample of patients diagnosed with UD. Methods: Smartphone data, clinical ratings, and questionnaires from patients with UD were collected six months following discharge from psychiatric hospitalization as part of a randomized controlled study. Smartphone data were collected daily, and clinical ratings (i.e., Hamilton Depression Rating Scale 17-item) were conducted three times during the study. We investigated associations between 1) smartphone-based patient-reported mood and activity and clinical ratings and questionnaires; 2) automatically generated smartphone data resembling physical activity, social activity, and phone usage and clinical ratings; and 3) automatically generated smartphone data and same-day smartphone-based patient-reported mood and activity. Results: A total of 74 patients provided 11,368 days of smartphone data, 196 ratings, and 147 questionnaires. We found that: 1) patient-reported mood and activity were associated with clinical ratings and questionnaires (p <0,001), so that higher symptom scores were associated with lower patient-reported mood and activity, 2) Out of 30 investigated associations on automatically generated data and clinical ratings of depression, only four showed statistical significance. Further, lower psychosocial functioning was associated with fewer daily steps (p=0,036) and increased number of incoming (p=0.032), outgoing (p=0.015) and missed calls (p=0.007), and longer phone calls (p=0.012); 3) Out of 20 investigated associations between automatically generated data and daily patient-reported mood and activity, 12 showed statistical significance. For example, lower patient-reported activity was associated with fewer daily steps, shorter distance travels, increased incoming and missed calls, and increased screen-time. Conclusion: Smartphone-based self-monitoring is feasible and associated with clinical ratings in UD. Some automatically generated data on behavior may reflect clinical features and psychosocial functioning, but these should be more clearly identified in future studies, potentially combining patient-reported and smartphone-generated data.